2020
DOI: 10.1088/1361-6579/ab8770
|View full text |Cite
|
Sign up to set email alerts
|

Automatic heart sound classification from segmented/unsegmented phonocardiogram signals using time and frequency features

Abstract: Objective: Heart abnormality detection using heart sound signals (phonocardiogram (PCG)) has been an active research area for the last few decades. In this paper, automatic heart sound classification using segmented and unsegmented PCG signals is presented. Approach: In this paper: (i) we perform an in-depth analysis of various time and frequency domain features, followed by experimental determination of effective feature subsets for improved classification performance; (ii) both segmented and unsegmented PCG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Heart sound signals are a kind of sequential data with a strong temporal correlation and can thus be suitably processed by RNNs. Indeed, they have been proven to be very effective and are commonly used for heart sounds classification [46][47][48][49][50].…”
Section: Rnn Methods For Heart Sounds Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Heart sound signals are a kind of sequential data with a strong temporal correlation and can thus be suitably processed by RNNs. Indeed, they have been proven to be very effective and are commonly used for heart sounds classification [46][47][48][49][50].…”
Section: Rnn Methods For Heart Sounds Classificationmentioning
confidence: 99%
“…However, compared with other non-deep learning methods, it eliminates the tedious process of manual feature extraction. Khan et al [47] used LSTM in combination with the MFCC features of the unsegmented data and achieved the best area under the curve score of 91.39% in the PhysioNet/CinC Challenge, performing better than other algorithms such as SVM, KNN, decision tree, and ANN for various time and frequency-domain features. Similarly, Raza et al [49] used the LSTM model to classify three kinds of heart sounds-namely, normal, murmur, and extrasystole-in PASCAL heart sound dataset B.…”
Section: Rnn Methods For Heart Sounds Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared the classification results of segmented and unsegmented heart sound signals and concluded that using segmented heart sound signals can contributes to better classification. However, in the experiment, they used the improved empirical wavelet transformation and standardized Shannon average energy to preprocess and automatically segment the signals to identify the systolic and diastolic interval of the signal, instead of the segmentation of the four states [35]. An example of a normal heart sound includes two heart sound cycles, and each cycle consists of the following heart sound components: S1, sys, S2, and dia.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the incorrect localization of the FHS was partially blamed for the poor classification performance. Based on this, researchers proposed a classification approach without the requirement of segmentation [ 32 , 33 , 34 , 35 , 36 ]. This paper proposes a classification system for heart sounds that does not require segmentation.…”
Section: Introductionmentioning
confidence: 99%